Mechanical and thermal properties of sugar palm fiber reinforced thermoplastic polyurethane composites: effect of silane treatment and fiber loading - A., Atiqah; M., Jawaid; S. M., Sapuan; M. R., Ishak (2018)
The aim of the present study was to develop sugar palm ﬁber (SPF) reinforced thermoplastic polyurethane (TPU) composites and to investigate the effects of ﬁber surface modiﬁcation by 2% silane treatment and ﬁber loading (0, 10, 20, 30, 40 and 50 wt%) on the mechanical and thermal properties of the obtained composites. Surface treatment was employed to improve the ﬁber-matrix interface, which was expected to boost the mechanical strength of the composites, in terms of tensile, ﬂexural and impact properties. Thermal properties were also investigated by thermal gravimetric analysis (TGA) and dynamic mechanical analysis (DMA) to assess the thermal stability of the developed composites. Furthermore, scanning electron microscopy (SEM) was used to study the tensile fracture samples of composites with a view towards evaluating the effects of ﬁber surface treatments on the ﬁber/matrix interfacial bonding. The ﬁndings of this study reveal that the silane treatment has determined good bonding and linkage of the cellulose ﬁber to the TPU matrix, hence contributing to enhanced mechanical and thermal properties of the composites. The composite formulation with 40 wt% sugar palm ﬁber loading showed optimum values such as 17.22 MPa for tensile, 13.96 MPa for ﬂexural, and 15.47 kJ/m2 for impact strength. Moreover, the formulations with higher ﬁber content exhibited satisfactory values of storage modulus and thermal degradation, while their good interfacial adhesion was evidenced by SEM images.